2021
DOI: 10.1186/s12903-021-01422-5
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and correlates of dental service utilisation among a national general adult population sample in Sudan

Abstract: Background Prompt dental service utilisation (DSU) is needed for the prevention and treatment of oral diseases, and it is therefore important to determine the facilitators and barriers of DSU. There is, however, scarce information available on DSU in Sudan. Therefore, this study aimed to investigate the prevalence and associated factors of DSU in a general population-based survey among 18–69 year-old persons in Sudan. Methods Cross-sectional nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
2
10
2
Order By: Relevance
“…Our exploratory study estimated that mothers were 1.2 times more likely to have ever received prenatal care compared to any kind of dental care (including both treatment-oriented and exclusively prevention-oriented visits). This estimate is consistent with other studies in Sudan and the Solomon Islands which found greater odds of utilization of dental care services given participation in preventive measures such as health screenings [ 43 , 44 ]. Our study also estimated that children were over 3 times more likely to be up-to-date with immunizations than to have received any kind of dental care.…”
Section: Discussionsupporting
confidence: 92%
“…Our exploratory study estimated that mothers were 1.2 times more likely to have ever received prenatal care compared to any kind of dental care (including both treatment-oriented and exclusively prevention-oriented visits). This estimate is consistent with other studies in Sudan and the Solomon Islands which found greater odds of utilization of dental care services given participation in preventive measures such as health screenings [ 43 , 44 ]. Our study also estimated that children were over 3 times more likely to be up-to-date with immunizations than to have received any kind of dental care.…”
Section: Discussionsupporting
confidence: 92%
“…In a household study conducted in South Africa by Olutula et al [ 13 ], it was determined that males rated their oral health as “good” compared to females. Pengpid and Peltzer, in a household study in Sudan, reported that females had a higher odds of poor self-reported oral health [ 14 ], which differed from the findings in this study. The differences in the above studies could be attributed to the differing ages groups across the various studies.…”
Section: Discussioncontrasting
confidence: 99%
“…A study from Canada revealed that immigrants who had dental problems were more likely to increase their use of dental services [ 19 ]. Another study in Sudan found that DSU in the 12 months preceding the study, or more than 12 months, was related to chewing difficulty [ 20 ]. A study from New Zealand demonstrated that non-regular dental attendees were related to higher Oral Health Impact Profile (OHIP) scores, indicating more impact and lower self-rated oral health scores [ 21 ].…”
Section: Introductionmentioning
confidence: 99%